Pengembangan Produk Jam Water Weker Dengan Metode Quality Function Deployment - Kalam Mahardika Saefullah; Monita Rahayu; Sutresna Juhara (Universitas Islam Syekh Yusuf Tangerang, 2023)
Alarm clocks becoming more modern as time, and fewer people use them because there are many tools to serve as time reminders, for example, cellphones, etc. However, this development has negative impact on the body, to the radiation produces. Therefore, author will develop this alarm clock to make it look more attractive to people who no longer use alarm clocks and don't only serve as a time reminder. Methodology process making this water alarm product includes many very important considerations because has go through several trial sessions with the alarm clock which will replaced replacing or increasing some of the materials for its manufacture, in particular a fish aquarium with a size of Â±200 mm will be made by adding more tools to help circulate water when the alarm sounds to find out the amount of consumer demand using the Quality Function Deployment (QFD) method. From the results the validity test output of questionnaire distributed to respondents, there are 13 valid attributes and 2 invalid attributes. Therefore, from the results of data adequacy test, it sufficient to carry out product designs according the wishes or needs of the customer, which can be seen in the HOQ (House of Quality) image.